Metáforas digitais do cotidiano - Ana Elisa Costa Novais (2018)
Our communicational landscape has been occupied by command buttons, system messages, progress indicators, mouse pointers, and other conventions of digital interfaces. Emerging in texts of a diverse nature, these semiotic resources created to mediate digital experiences have been explored in producing meaning about our experiences in various language activities. In this research, of an applied nature, with a qualitative approach and interpretative basis, I analyze 31 texts took from advertising pieces, t-shirt prints, protest posters, memes, remixes, comics and cartoons. The research was based on the cognitive perspective of language, through the intersection of the Conceptual Metaphor Theory, the Multimodal Metaphor Theory and the Conceptual Integration Theory. From the intersection of these theories, the concepts of imaging schemes, emerging structures, compressions, conceptual and metaphorical projections, and integration networks were highlighted. Within this framework, we tried to answer the following questions: a) what meanings emerge from our digital experiences? b) how are emerging metaphors of digital experiences appropriated by other metaphorical processes? and d) what typically digital semiotic features are remediated in multimodal texts? Following these questions, the objectives were: a) to situate the digital interfaces in the Language / Cognition / Culture tripod, under the scope of Applied Linguistics; b) to identify metaphorical projections, imaging schemes and conceptual domains typically linked to digital interface conventions; c) to know possibilities of using digital conventions in multimodal texts. The texts were categorized based on the Interaction Design and Ergonomics models, and framed in the dimensions of a) surfaces, objects and entities; b) metaphors of manipulation and access; c) metaphors of digital processes (save, format, delete, undo and process in progress). As results, I highlight: a) SURFACE metaphors generate propositions emerging from the schematic relations between overlapping conventions and contents highlighted by semiotic features that indicate their activation; b) ARCHIVE metaphor, used to conceptualize objects and entities, lends dimensions digital properties to elements of the physical world, such as people and animals, or to abstract concepts such as love and rancor; c) the emerging sensation of manipulation and access activates the imagery schemes ATTRACTION and COMPULSION and establish a communicative pact in which a need for response provides limited alternatives that restrict the production of meanings; d) metaphors that include PROCESSES generate emerging structures that integrate other metaphors such as OBJECTS, SURFACES AND HANDLING; e) the metaphor UNDO updates the metaphor of "going back in time" to "undo the last action"; f) the CURRENT PROCESS metaphor, instantiated by the progress indicator, compresses spatio-temporal dimensions impossible to be measured by physical time measurement devices. These results indicate that the presence of interface conventions in multimodal texts mobilizes many and varied conceptual structures. To attribute meanings to the world and to ourselves through metaphors assumes dimensions in which the references are given by an emergent conceptual domain: that of the digital experiences mediated by interfaces.